Alimentación, condición corporal y principales parásitos del pejerrey (Odontotesthes bonaeriensis) del embalse San Roque (Argentina) - Bethular, A. (2014)
San Roque reservoir (31º22`S, 64º27´W, 2478 ha) is located in the province of Córdoba (Argentina). The silverside Odontesthes bonariensis is the dominant and most important sport fishing species in this reservoir and sustains a strong socioeconomic activity. The study aims were description of the food items, the seasonal variation of the parasitic burden and prevalence, as well as the body condition in O. bonariensis. A total of 242 silversides specimens were caught during the four study seasons. Food items were assessed by means of index of categorization (ICI). The degree of parasitism was measured using prevalence, intensity and density. The weight-length relationship and relative condition factor were calculated. Digestive contents revealed the presence of Copepoda and Cladocera, essentially dominated by Bosmina huaronensis over Bosmina longirostris. The presence of phytoplankton and Palaemonetes sp. reproduces findings reported for other environments. The silverside’s body condition showed significant differences between year seasons (P<0.001), being better in winter and spring. Lernaea cyprinacea was observed around the dorsal and pectoral fins, and Cangatiella macdonaghi in the digestive content. Both parasites were highly prevalent during summer months.